2020
DOI: 10.3389/fmars.2020.00107
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Reliable Estimates of the Spatial Distribution of Kelp Biomass

Abstract: Kelp forests are highly productive systems that are important ecologically and commercially as well as in a blue carbon perspective. Given their importance, there is an urgent need to achieve reliable estimates of the spatial distribution of their biomass. Species distribution modelling is a powerful tool for producing such estimates, but it requires a solid framework, including important environmental covariates that have a direct effect on their biomass, a proper sampling strategy, and an independent evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
(70 reference statements)
1
12
0
Order By: Relevance
“…All the measured size-related kelp canopy plant characteristics, as well as kelp canopy density, are reduced with water depth. This was in accordance with previous studies, as the amount of light that reaches the seafloor, and thus available for kelp photosynthesis, is reduced with depth (Kain, 1971a;Vigander, 2007;Bekkby et al, 2009;van Son et al, 2020). Also, the abundance of epiphytes on the stipe decreased with depth, which is most likely directly caused by light limitation for photosynthetic species.…”
Section: Kelp Characteristics Along Depth and Wave Gradientssupporting
confidence: 92%
See 1 more Smart Citation
“…All the measured size-related kelp canopy plant characteristics, as well as kelp canopy density, are reduced with water depth. This was in accordance with previous studies, as the amount of light that reaches the seafloor, and thus available for kelp photosynthesis, is reduced with depth (Kain, 1971a;Vigander, 2007;Bekkby et al, 2009;van Son et al, 2020). Also, the abundance of epiphytes on the stipe decreased with depth, which is most likely directly caused by light limitation for photosynthetic species.…”
Section: Kelp Characteristics Along Depth and Wave Gradientssupporting
confidence: 92%
“…However, in the present study, less than 2% of the area suitable for kelp forest growth had a higher exposure than the highest wave exposure level sampled (1.8 km 2 /sec), thus the lack of data from such areas will not have biased the overall conclusions. Other Norwegian studies found up to a doubling in biomass in moderately wave exposed compared to more sheltered areas, with a levelling off toward more exposed sites (Andersen, 2007;Pedersen et al, 2012;Norderhaug et al, 2012;van Son et al, 2020). A similar, but somewhat weaker pattern was found for L. hyperborea biomass in north-western France by Gorman et al (2013) and for canopy density in the United Kingdom (Smale et al, 2016).…”
Section: Kelp Characteristics Along Depth and Wave Gradientsmentioning
confidence: 62%
“…Further investigation on the best way to incorporate such categorical variables is advised, along with possible refinement of the AOA threshold. Possible solutions include using ordered variables, or conversion of the sediment grain size classes to generalised sediment fractions [73]. We also note that the survey design (video stations) was made long before these oceanographic datasets were available.…”
Section: Spatial Validity and Uncertainty Indicesmentioning
confidence: 99%
“…Changes in environmental conditions can affect not only the suitability of kelp habitat, but also the abundance of the species that are present. Macroalgal abundance can be estimated in terms of density, biomass and percent cover (e.g., Gorman et al, 2013;Bajjouk et al, 2015;Young et al, 2015;Krumhansl et al, 2016;van Son et al, 2020). However, quantitatively calculating these various estimates of abundance for currently unstudied areas and future scenarios cannot be done using most SDM tools, which rely on presence/absence input data.…”
Section: Introductionmentioning
confidence: 99%